In situ temperature measurements through i-anvils in diamond anvil cells - Gondé, Charlotte; Bureau, H.; Burchard, Michael; Henry, S.; Simon, G.; Meijer, J.; Kubsky, S. (Review of scientific instruments, 2010)
This study is devoted to in situ temperature measurement in diamond anvil cells (DACs) with intelligent anvils (i-anvils). I-anvils consist of diamonds implanted with B and/or C ions, situated below the diamond's surface at a depth of 1-3 microm; forming sensors which are placed below the culet at the location of the DAC's sample chamber. I-anvils can be employed as temperature or pressure sensors, exploiting their electrical properties. We have tested the sensor's behavior with temperatures up to 900 degrees C, at ambient pressure and up to 6 GPa in real experimental conditions in two types of DAC. For this purpose, we performed experiments in four different i-anvils at temperatures up to 900 degrees C. We have compared the signal measured by the sensors with the temperature measured by a thermocouple attached to the i-anvil. The temperature gradient between the sample chamber and the thermocouple position was taken into account by phase transition measurements of calibration standards. Reproducible laws of current variation with temperature have been established. We conclude that i-anvils are reliable and sensitive to measure the temperature in-situ in DACs with an accuracy of better than 1 degree C.
Gesehen am 26.04.2023